Binding characteristics of the new thromboxane A2/prostaglandin H2 receptor antagonist (3H)BAY U 3405 to washed human platelets and platelet membranes - Theis, Jochen G.; Dellweg, Hansgeorg; Perzborn, Elisabeth; Groß, Rainer (Biochemical pharmacology, 1992)
The new thromboxane A2 antagonist [3H]BAY U 3405 was characterized for its binding to washed human platelets and platelet membranes. In washed platelets the specific binding was reversible, selective and stereospecific, but not saturable. The dissociation constant (Kd) was 6 ± 2.5 nM, the number of specific binding sites 1177 ± 306 per platelet. Three structurally different thromboxane A2 (TXA2)/prostaglandin H2 (prostaglandin endoperoxide) (PGH2) receptor ligands completely inhibited the specific binding of [3H]BAY U 3405 in a concentration-dependent manner, indicating that the observed high affinity binding site is the TXA2/PGH2 receptor. In platelet membranes, however, specific [3H]BAY U 3405 binding showed saturability in addition to reversibility, selectivity, and stereospecifity. The Kd of the binding was 9.6 ± 2.3 nM in kinetic studies and 8.7 ± 3.7 nM in saturation studies, the inhibition constant (Ki) was 10 ± 1.1 nM in displacement studies. The TXA2/PGH2 receptor agonists U 46619 and CTA2, and the antagonists Daltroban (BM 13505), I-PTA-OH and SQ 29548 all completely inhibited the specific binding of [3H]BAY U 3405 thus defining the observed binding site as the TXA2/ PGH2 receptor. In conclusion, the data suggest that the previously reported TXA2 antagonism of BAY U 3405 is mediated by binding to a specific high affinity binding site of human platelets and platelet membranes that represents the TXA2/PGH2 receptor.